Development of forward and reverse genetic tools for Eubacterium limosum - Millard, Christopher (2018)
Eubacterium limosum is an anaerobic, acetogenic Gram-positive bacterial species which is able to subsist on mixtures of CO, CO2 and H2. Additionally, it is able to grow on methanol. While growing autotrophically on these single-carbon feedstocks, E. limosum produces a range of fermentation products of industrial interest. However, no techniques for genetic manipulation of E. limosum have yet been published, and current studies concentrate on the optimisation of fermentation conditions. Here, techniques for both random insertional mutagenesis and directed genetic manipulation of E. limosum are described and exemplified. The transposon mutagenesis procedure demonstrated during this study should enable the generation of large insertional mutant libraries, which will in turn allow the study of gene essentiality during autotrophic growth on single-carbon gases and methanol. The directed genetic manipulations undertaken during this study include gene knockout via Allele-Coupled Exchange (ACE) and in-frame gene deletion via CRISPR-Cas9. In addition to the establishment of genetic techniques in E. limosum, a novel Gram-positive replicon was isolated from a cryptic plasmid of Clostridium carboxidivorans during this study. This Gram-positive plasmid replicon is described and characterised. The replicon was modularised in accordance with the clostridial pMTL80000 plasmid system, and has proven suitable for use in E. limosum and in a range of other solventogenic and acetogenic clostridia. The copy number of the novel replicon was determined in E. limosum and C. beijerinckii, as was the copy number of the widely-used pCB102 replicon.